Behcet's Disease: Difficulties In Diagnosis And Patient Management (Clinical Example) - Nurmatov U. B; Nurmatova N.F (Zien Journals, 2025)
The article describes a clinical case of Behçet's disease, a rare systemic vasculitis characterized by recurrent orogenital ulcers, ocular and skin manifestations. Detailed anamnesis, clinical examination, laboratory tests and treatment are presented
Keywords: Behçet’s disease; pathogenesis; clinic; treatment